Biogenic synthesis of silver nanoparticles (AgNPs) from Allium jacquemontii extract and its assessment in different biological activities - Asif Kamal; Moona Nazish; Tehmina Siddique; Muhammad Azhar Khan; Narjis Khatoon; Ghulam Mujtaba Shah; Jawaher Alzahrani; Wasim Akhtar; Shoaib Noor; Muhammad Tahir Naseem; Wajid Zaman (Scientific Reports)
Abstract Nanotechnology is a vibrant and fast-developing field in science with diverse applications. Silver nanoparticles (AgNPs) are becoming gradually valuable because of their exceptional antimicrobial properties and remarkable physical characteristics. This study reports the phytochemical screening of Allium jacquemontii plant extract for the preparation of AgNPs. The prepared nanoparticles (NPs) were characterized via UV- spectroscopy, X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM) and were evaluated for antimicrobial and pharmacological activities. HPLC analysis showed that A. jacquemontii had the lowest quantity of ferulic acid (10.3 ppm) and the highest concentration of chlorogenic acid (317.9 ppm). The prepared AgNPs exhibited excellent antifungal potential against Aspergillus niger, with maximum growth inhibition of 64.4% while strong antibacterial activity of 14.3 mm against Escherichia coli at a dose of 10 mg/ml was found. Similarly, the highest antiparasitic activity was 75.41 ± 1.16 against Promastigote and 71.13 ± 0.12 against Amastigote at 200 µg/mg. Inhibition of glucosidase, and amylase was observed, suggesting potential antidiabetic properties. The AgNPs were found to be biofriendly with red blood cells (RBCs) of a healthy human. This study indicates the potential of A. jacquemontii inflorescence derived AgNPs.